The Development of Concept Development – Collaborative Decision-Making Problem Solving (CD-CDMPS) To Improve The Prospective Physics Teachers’ Decision-Making Skills - Yulianti Yusal (WaPFi (Wahana Pendidikan Fisika), 2022)
ABSTRACTResearch on the development of a concept development model - collaborative decision making problem solving (CD-CDMPS) to improve the prospective physics teachers’ decision-making skills has been carried out. This study aims to develop a teaching model that is effective in improving the decision-making skills of student-teachers. The method used in this research is R D (reseach and development) which includes the following stages: (1) needs analysis; (2) product development (design, develop, and product validating); (3) field test of the products produced; and (4) product improvement based on the results of field test. The research subjects were 23 prospective physics teachers on a limited scale trial and 76 prospective physics teachers on a large-scale trial at a university in Makassar, South Sulawesi. The research instrument used was a 5-point decision-making skill test in the form of a description. The results showed that after the application of the developed CD-CDMPS lecture model, most students achieved improved decision-making skills in the high category. Thus, the CD-CDMPS model developed can be effectively used to improve students’ decision-making skills.Keywords: CD-CDMPS model, Decision-making Skills, Prospective Physics Teachers